Microstructural Investigations of Rapidly Solidified Al-Co-Y Alloys - B. Avar; M. Gogebakan; M. Tarakci; Y. Gencer; S. Kerli (Advances in Materials Science and Engineering)
The alloys with different compositions in the Al-rich corner of the Al-Co-Y ternary system were prepared by conventional casting and further processed by melt-spinning technique. The microstructure and the thermal behavior of the alloys were analyzed by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and differential thermal analysis (DTA). It was found that only rapidly solidified Al85Co7Y8 alloy exhibited the best glass forming ability (GFA) and a fully amorphous structure. Besides, Al85Co13Y2 and Al85Co2Y13 alloy ribbons were fully crystalline, whereas Al85Co10Y5 and Al85Co5Y10 alloy ribbons consisted of some crystalline phases within an amorphous matrix. The SEM results showed the same trend that the crystalline phase fraction decreases with the approaching into best glass former. From DSC results, only Al85Co7Y8 amorphous alloy exhibited a glass transition temperature (Tg) at 569 K, and its supercooled liquid region (ΔTx=Tx−Tg) was found to be 17 K. Moreover, other calculated GFA parameters for this alloy system were also discussed.